Aplikasi Brief Pain Inventory (BPI) untuk Mengidentifikasi Nyeri Kronis pada Pasien Kanker Payudara - Ni Nyoman Sri Ayu Desianti; I Dewa Putu Gede Putra Yasa; I Wayan Surasta; VM Endang SP Rahayu (Jurnal Gema Keperawatan, 2023)
Chronic pain is the main complaint of breast Cancer patients. Appropriate pain assessment is needed in palliative care of cancer patients. This study aims to describe the characteristics of pain in breast cancer patients who are studied with BPI at Bali Mandara Hospital in 2023. This research method uses a quantitative method which is carried out at the Surgical Oncology Polyclinic at Bali Mandara Hospital. This research activity was carried out in April 2023 using a purposive sampling technique of 44 respondents. The BPI Pain Inventory Brief Questions cover several aspects of pain assessment, many factors can be identified that affect pain objectively. This is very helpful in managing pain by the Nursing team. The results showed characteristic age respondents 30-40 years old was 7 (15,9%), 41-50 years old was 17 (38,6%), 51-60 years old was 13 (29,5%), 61-70 years old was 4 (9,1%) and 71-80 years old was 3 (6,9%). Respondents' characteristic length of the used contraceptive method was mean: 2 years 5 months, minimum at 5 years dan maximum at 72 months. that out of 44 respondents, 25 respondents (56.8%) experienced mild pain with a score of 1-3, moderate pain as many as 18 respondents (40.9%) with a score of 4-6, and severe pain as much as 1 (2.3%) with a score of 7-10. It can be concluded that this study showed that most of the respondents experienced pain that was not too severe. This is very helpful in managing pain by the nursing team.